PENGARUH PROSENTASE FRAKSI MASSA NaOH (NATRIUM HIDROKSIDA) SEBAGAI KATALIS DALAM PROSES ELETROLISIS DENGAN MENGGUNAKAN ELEKTROLISER TIPE DRY CELL - Novan Yoga Prasetya; Abdul Wahab; Ena Marlina (UNIVERSITAS ISLAM MALANG, 2017)
This study aims to determine the effect of variations in the percentage of the mass fraction of NaOH (sodium hydroxide) to the performance of the HHO (Brown Gas) produced using electrolysis method by using the tool elektroliser type of dry cell electrode and the neutral plate using 304 stainless steel with insulation between electrodes using a rubber O- ring. HHO gas production performance observed in this study is the electric power used to produce HHO gas from each vasiari percentage of mass fraction, the rate of production of each variation percentage of mass fraction as well as the efficiency of HHO gas production of each variation percentage mass fraction. Electrolysis is the decomposition of the compound water (H2O) into molecules of hydrogen and oxygen (HHO) electricity use direct current (DC) in the electrolyte solution. This process happens when two electrodes (anode and cathode) are placed in distilled water and direct current (DC) which directly flows through the system. In this study, sodium hydroxide as a catalyst dissolved in distilled water in to speed the process of electrolysis. Percentage mass fraction of sodium hydroxide varies from 4% - 6%. The results showed that the electric power used for the production of HHO gas increased seirirng increase in the percentage of the mass fraction of sodium hydroxide and reaches a maximum value at porsentase mass fraction of 6%, amounting to 93 watts, at a rate produks HHO gas and efficiency HHO generator increases and reaches a maximum value the percentage of the mass fraction of sodium hydroxide 4% at 203.75 ml / s.